PERANAN KOMUNIKASI BADAN KESWADAYAAN MASYARAKAT DALAM MENSOSIALISASIKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN DI KOTA BANJARMASIN - Hudri hudri; Muhammad Ma'ruf Abdullah; M.S. Sailillah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
One of the executing agency is the PNPM Urban Community Self-Reliance Agency (BKM). BKM is a collective leadership council society resident population of the village, and as the BKM institutions can act as a representation of civil society village residents. In some villages in the district east Banjarmasin, found that in his travels, BKM various constraints both internal and external, among others: internal constraints such as: yet the prevalence of human resource capabilities associated with the BKM BKM concepts so that the dependence on the coordinator is still large. External constraints such as indifference from the majority community towards poverty reduction so as to make some programs, particularly environmental obstacles. Based on the research results, it can be concluded that. BKM performed the role of communication in disseminating the National Program for Community Empowerment in Urban Banjarmasin run effectively enough to remember the people who began to use the program PNPM Urban community even ask for increasingly easy in the governance practices as well as the implementation of the PNPM Urban continuously improved and sustained. Key words: Communications, National Program for Community Empowerment Urban